(untitled) - Cooper, Jason; 1942- (Vero Beach, Fla., 1991)
An introduction to cactuses, a plant family of some 2000 species which share the ability to store water.
Translation of: Cactus.
Includes index.
Keywords: Cactus; Juvenile literature; Cactus; Spanish language materials